L'importanza del vaccino anti Covid-19 nei pazienti affetti da malattia del rene policistico autosomico dominante dell'adulto (ADPKD) - Maria Teresa Sciarrone Alibrandi; Giancarlo Joli; Rodolfo F. Rivera; Elena Brioni; Romina Bucci; Marta Vespa (AboutScience Srl, 2021)
The SARS-CoV-2 (Covid-19) infection affected about 106 million people worldwide and the total amount of casualties now sits at a staggering 2 millions. Chronic Kidney Disease (CKD) emerged as the first risk factor in worst patients, not considering old age. Kidney disease and acute kidney injury have been correlated with a higher chance of death. This combination of CKD and higher Covid-19 related mortality requires immediate response from a prevention point of view at first and then from a therapeutic one. There is not a clear relation between Covid-19 and ADPKD. What can be inferred is the following: Covid uses the ACE2 receptors on cell membranes to "lock on" its target. It is well-established in fact that the RAAS is more active in ADPKD patients and it may represent an additional risk factor for these patients. At the moment three Covid-19 vaccines have been approved, and two of them have been already administered, such as Pfizer BioNTech and Moderna, sharing the same mechanism. AstraZeneca released a third option. All of them are completely safe and reliable, each one with its own feature. Therefore, considering how delicate ADPKD patients are, vaccination is strongly recommended.